Knowledge management and innovative behavior: police reform efforts in Puerto Rico. Issue 5 (16th August 2021) - Castro, Luis; Santos-Corrada, Maria; Flecha-Ortiz, Jose A.; Lopez, Evelyn; Gomez, Jose; Aponte, Brunilda
Abstract : Purpose: Knowledge management has historically been approached in private firms as a key factor for business management. However, this is not the case for government institutions. The existing literature on the transfer of knowledge appears as a topic little addressed in government and even to a lesser degree within the police forces. This study aims to evaluate the relationship between motivation, knowledge absorption, knowledge transfer and innovative behavior in a public organization such as the Puerto Rico Police. Design/methodology/approach: This quantitative research using the survey technique had the participation of 300 police officers from the 13 police regions of Puerto Rico and the research model was analyzed through partial least squares structural equation modeling. Findings: The results contribute to the growth of the currently limited literature at identifies how motivation, knowledge absorption, knowledge transfer and institutional support influence innovative behavior. Originality/value: The study discusses a series of implications on less explore the issue in how the transfer of knowledge becomes a key force to produce change and the success of all reforms. Various implications for the success of public administration in bringing a change from a bureaucratic culture to an advanced one are also discussed.